IMPLEMENTASI PENINGKATAN KEMAMPUAN MEMBACA DAN MENULIS PESERTA DIDIK MELALUI KEGIATAN BACA SEBELUM PEMBELAJARAN - ROFIQ, ASNGADI (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study aims to investigate the effectiveness of implementing newspaper reading activities before learning in improving the reading and writing skills of junior high school students. Newspaper reading activities were chosen as an intervention because of their potential in providing reading materials that are actual, diverse, and relevant to students' daily lives. This study used mixed methods, combining quantitative and qualitative approaches. Quantitative data were collected through reading and writing ability tests before and after the intervention, while qualitative data were obtained through observation, interviews, and document analysis. The results of the study showed the Effectiveness of Newspaper Reading Activities, Newspaper reading activities before learning have proven effective in improving the reading and writing skills of junior high school students. This is supported by a significant increase in the results of reading and writing ability tests, as well as an increase in the quality of students' writing. Increasing Reading Interest and Motivation, Newspaper reading activities can increase students' reading interest and motivation. Current and diverse reading materials provide opportunities for students to learn about issues that are relevant to their lives, thereby increasing their interest in reading activities. Developing Critical Thinking Skills: Newspaper reading activities encourage students to think critically and convey ideas in writing. Analysis and discussion of issues raised in newspapers helps students to develop their critical thinking skills.